2015
DOI: 10.1038/ncomms8565
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic elimination-based coupling control in densely packed subwavelength waveguides

Abstract: The ability to control light propagation in photonic integrated circuits is at the foundation of modern light-based communication. However, the inherent crosstalk in densely packed waveguides and the lack of robust control of the coupling are a major roadblock toward ultra-high density photonic integrated circuits. As a result, the diffraction limit is often considered as the lower bound for ultra-dense silicon photonics circuits. Here we experimentally demonstrate an active control of the coupling between two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 41 publications
0
61
0
Order By: Relevance
“…Furthermore, it is shown that STIRAP is exceedingly robust against controlling parameters under perturbations. The SITRAP has already been widely used in various domains, such as atomic molecular and optical physics [27,28], waveguide coupler [29,30], graphene electronic and optical effect [24,31].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is shown that STIRAP is exceedingly robust against controlling parameters under perturbations. The SITRAP has already been widely used in various domains, such as atomic molecular and optical physics [27,28], waveguide coupler [29,30], graphene electronic and optical effect [24,31].…”
Section: Introductionmentioning
confidence: 99%
“…Consider the ‘hiding’ (or ‘decoupling’) of some elements inside densely packed coupled optical systems 5, 711 . Transformation optics in this scenario provides the severely intricate solution even for the approximated case 12 : the coating of target elements with spatially-varying, highly anisotropic metamaterials of extreme material parameters (effective permittivity ~0), which derives the ‘microscopic’ removal of the coupling to the target elements.…”
Section: Introductionmentioning
confidence: 99%
“…The wave propagation direction along a chain of plasmonic particles with tightly localized photonic modes is determined by the sign of the coupling factor, which stems from the overlap of the evanescent tails of tight‐binding photonic modes. Although the coupling strength can be easily tuned by adjusting the interparticle distance, it remains difficult to flip the sign of coupling factor and consequently switch between forward and backward wave propagations.…”
mentioning
confidence: 99%